Dynamics of Moderatism in the Kalam Thought: From Classical to Contemporary - Burhanuddin, Nunu; Hendri, Novi; Gazali, Gazali (Islamic Thought Review, 2023)
Moderatism is an essential foundation for religious expression among religious people in various fields of life, both in understanding and application. As part of the religious community, Mutakallimin from the classical to contemporary eras have provided valuable experiences for other Muslims. This paper aims to explore the experiences of the Mutakallimin regarding moderatism in the classical and contemporary eras. The writing method in this study uses literary methods and approaches to classical and contemporary Islamic literature. The results of the study explain that the Mutakallimin has demonstrated moderatism experiments marked by the emergence of the Khawarij Ibadiyah sect, Moderate Murjiah, Moderate Shia, the Mu'tazilah conception of rationality, the balance between Jabariyah and Qadariyah which is explored in the face of Asy'ariyah and Maturidiyah, as well as contemporary Kalam reform models which are based on theocentric and anthropocentric Kalam domains.